GIS_EM (Geographic information system for environmental monitoring) - A software implemented at Paulínia refinery (REPLAN) for management of environmental data - Furlan, L. T.; Jungklaus, C. D D G; Ferreira, J.; Chang, H. K. [UNESP] (My University, 2005)
The computational program called GIS_EM (Geographic Information System for Environmental Monitoring), a software devised to manage geographic information for monitoring soil, surface, and ground water, developed for use in the Health, Safety, and Environment Division of Paulinia Refinery is presented. This program enables registering and management of alphanumeric information pertaining to specific themes such as drilling performed for sample collection and for installation of monitoring wells, geophysical and other tests, results of chemical analyses of soil, surface, and groundwater, as well as reference values providing orientation for soil and water quality, such as EPA, Dutch List, etc. Management of such themes is performed by means of alphanumeric search tools, with specific filters and, in the case of spatial search, through the selection of spatial elements (themes) in map view. Documents existing in digital form, such as reports, photos, maps, may be registered and managed in the network environment. As the system centralizes information generated upon environmental investigations, it expedites access to and search of documents produced and stored in the network environment, minimizing search time and the need to file printed documents. This is an abstract of a paper presented at the AIChE Annual Meeting and Fall Showcase (Cincinnati, OH 10/30/2005-11/4/2005).
Keywords: Computational program; Management of environmental information; Search tools; Spatial elements